Associations between metabolomic-identified changes of biomarkers and arterial stiffness in subjects progressing to impaired fasting glucose - Jung, Saem; Kim, Minjoo; Lee, Young Ju; Lee, Sang-Hyun; Lee, Jong Ho (Clinical endocrinology (Oxford), 2015)
Summary Objective We investigated correlations between age‐related changes in circulating metabolites and arterial stiffness in impaired fasting glucose (IFG). Design, subjects, measurement This prospective cohort study included 602 healthy, normal fasting glucose (NFG) subjects (30–65 years old) who underwent triennial medical evaluation. After 3 years, 9·3% of subjects developed IFG (n = 56). Age, gender, BMI and fasting glucose were used to match the remaining NFG subjects (n = 546) that were included for the control group (NFG group, n = 80). Results After 3 years, levels of fasting glucose, insulin and malondialdehyde, and brachial–ankle pulse wave velocity (baPWV) were significantly greater in the IFG group than in the NFG group after adjusting for baseline values. The IFG group had a greater increase in lactosylceramide (P = 0·001, q < 0·05) and a greater reduction in phosphatidylcholine (PC) (18:0/20:4) than the NFG group. Multiple linear regression analysis showed that the change in baPWV was independently and positively associated with changes in fasting glucose and lactosylceramide. In all subjects, lactosylceramide levels positively correlated with changes in baPWV and fasting glucose, while premenopausal women were not shown, and negatively correlated with changes in PC and LDL particle size. Conclusions This study indicates that age‐related increase in circulating lactosylceramide is an independent predictor of increased arterial stiffness in subjects with impaired fasting glucose.